Reactivation of hepatitis B virus infection in patients with hemo-lymphoproliferative diseases, and its prevention - Sagnelli, Caterina; Pisaturo, Mariantonietta; Calò, Federica; Martini, Salvatore; Sagnelli, Evangelista; Coppola, Nicola (World journal of gastroenterology : WJG, 2019)
Reactivation of hepatitis B virus (HBV) replication is characterized by increased HBV-DNA serum values of about 1 log or by HBV DNA turning positive if previously undetectable in serum, possibly associated with liver damage and seldom life-threatening. Due to HBV reactivation, hepatitis B surface antigen (HBsAg)-negative/anti-HBc-positive subjects may revert to HBsAg-positive. In patients with hemo-lymphoproliferative disease, the frequency of HBV reactivation depends on the type of lymphoproliferative disorder, the individual's HBV serological status and the potency and duration of immunosuppression. In particular, it occurs in 10%-50% of the HBsAg-positive and in 2%-25% of the HBsAg- negative/anti-HBc-positive, the highest incidences being registered in patients receiving rituximab-based therapy. HBV reactivation can be prevented by accurate screening of patients at risk and by a pharmacological prophylaxis with anti-HBV nucleo(t)sides starting 2-3 wk before the beginning of immunosuppressive treatment and covering the entire period of administration of immunosuppressive drugs and a long subsequent period, the duration of which depends substantially on the degree of immunodepression achieved. Patients with significant HBV replication before immunosuppressive therapy should receive anti-HBV nucleo(t)sides as a long-term (may be life-long) treatment. This review article is mainly directed to doctors engaged every day in the treatment of patients with onco-lymphoproliferative diseases, so that they can broaden their knowledge on HBV infection and on its reactivation induced by the drugs with high immunosuppressive potential that they use in the care of their patients.